Effect of Different Dietary n-6 to n-3 Fatty Acid Ratios on the Performance and Fatty Acid Composition in Muscles of Broiler Chickens - Mandal, G P (Asian-Australasian journal of animal sciences, 2014)
The objective of this study was to investigate the different dietary ratios of n-6 to n-3 (n-6/n-3) fatty acid (FA) on performance and n-6/n-3 FA in muscles of broiler chickens. A total of 300 one-day-old Cobb chicks were randomly assigned to 3 treatments of 10 replicates in each (10 birds/replicate). Birds were fed on a corn-soybean meal-based diet containing 1% oil during starter (day 1 to 21) and 2% oil during finisher (day 22 to 39) phases, respectively. Treatments of high, medium and low dietary n-6/n-3 FA were formulated by replacing rice bran oil with linseed oil to achieve n-6/n-3 FA close to >20:1, 10:1 and 5:1, respectively. Average daily gain, average daily feed intake, and feed conversion ratio were similar (p>0.05) among the treatments. Serum glucose, cholesterol and triglycerides concentrations were not affected (p>0.05) by dietary treatments. In breast, concentration of C18:3n-3 was significantly greater (p = 0.001) for medium and low vs high n-6/n-3 FA, while concentrations of C20:5n-3, C22:6n-3, total n-3 FA, and n-6/n-3 FA were significantly higher for low vs medium, and medium vs high dietary n-6/n-3 FA. In contrast, concentrations of C18:2 and mono-unsaturated FA (MUFA) were lower for low vs high dietary n-6/n-3 FA. In thigh muscles, concentrations of C20:5n-3 were higher (p<0.05) for medium and low vs high dietary n-6/n-3 FA, and concentrations of C18:3n-3, C22:6, and n-3 FA were greater (p<0.05) for medium vs high, low vs medium dietary n-6/n-3 FA. However, concentrations of C18:1, MUFA, n-6/n-3 were lower (p<0.05) for low and medium vs high dietary n-6/n-3 FA. In conclusion, lowering the dietary n-6/n-3 FA did not affect the performance of chickens, but enhanced beneficial long-chain n-3 FA and decreased n-6/n-3 FA in chicken breast and thigh, which could be advantageous for obtaining healthy chicken products